Guide for the assessment of cacao quality and flavour - Cacao of Excellence (2023)
The Guide includes detailed protocols and procedures for evaluating cacao in various forms, such as unroasted cacao bean coarse powder, cacao mass, and chocolate. These methodologies have been developed over several years by a diverse group of experts, enabling objective assessments of cacao quality and flavour. It provides a universal language for describing cacao attributes, for a shared understanding among cacao professionals worldwide. This Guide serves as a comprehensive resource for individuals, associations and organisations interested in internationally aligned capacity building, with the objective of setting up cacao quality and flavour assessment facilities and sensory evaluation panels. The development of this Guide has been a collective endeavour spanning several years, drawing upon the expertise of stakeholders across the cacao sector. It began in September 2015 with the formation of an informal working group, coordinated by Cacao of Excellence to explore the establishment of international standards for assessing cacao quality and flavour. The group conducted a comprehensive review of existing standards in cacao, coffee, olive oil and wine. In 2016, a first proposal for a harmonised standard for cocoa quality and flavour assessment was developed, led by Dr Darin Sukha of the Cocoa Research Centre at the University of the West Indies in Trinidad and Tobago (CRC). In 2017 and 2018, individual protocols were developed based on this proposal and reviewed extensively by members of the working group and diverse stakeholders from the cacao sector. Between 2018 to 2022, a meticulous external review and refinement process involved more than 100 people from over 30 countries, resulting in this Guide. By 30 June 2023, more than 1,500 people from 105 countries had downloaded the protocols.